2021
DOI: 10.3390/antiox11010065
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota-Derived PGF2α Fights against Radiation-Induced Lung Toxicity through the MAPK/NF-κB Pathway

Abstract: Radiation pneumonia is a common and intractable side effect associated with radiotherapy for chest cancer and involves oxidative stress damage and inflammation, prematurely halting the remedy and reducing the life quality of patients. However, the therapeutic options for the complication have yielded disappointing results in clinical application. Here, we report an effective avenue for fighting against radiation pneumonia. Faecal microbiota transplantation (FMT) reduced radiation pneumonia, scavenged oxidative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…For example, 10% to 30% of patients with lung or breast cancer who receive radiation therapy will develop radiation-induced pneumonitis, and they are likely to develop radiation-induced lung fibrosis ( Fleckenstein et al, 2007 ; Chao et al, 2017 ). In mice with local chest irradiation, Chen et al (2021) found that Akkermansia, Desulfovibrio and Parasutterella increased and Rikenella decreased at the genus level and that Distasonis , Goldsteinii , and Rodentium decreased at the species level. These changes were ameliorated after FMT ( Chen et al, 2021 ).…”
Section: Microbiome Alteration In Pulmonary Fibrosismentioning
confidence: 98%
See 1 more Smart Citation
“…For example, 10% to 30% of patients with lung or breast cancer who receive radiation therapy will develop radiation-induced pneumonitis, and they are likely to develop radiation-induced lung fibrosis ( Fleckenstein et al, 2007 ; Chao et al, 2017 ). In mice with local chest irradiation, Chen et al (2021) found that Akkermansia, Desulfovibrio and Parasutterella increased and Rikenella decreased at the genus level and that Distasonis , Goldsteinii , and Rodentium decreased at the species level. These changes were ameliorated after FMT ( Chen et al, 2021 ).…”
Section: Microbiome Alteration In Pulmonary Fibrosismentioning
confidence: 98%
“…In mice with local chest irradiation, Chen et al (2021) found that Akkermansia, Desulfovibrio and Parasutterella increased and Rikenella decreased at the genus level and that Distasonis , Goldsteinii , and Rodentium decreased at the species level. These changes were ameliorated after FMT ( Chen et al, 2021 ).…”
Section: Microbiome Alteration In Pulmonary Fibrosismentioning
confidence: 98%
“…Therefore, regulating the gut microbiota may be an important method to upgrade the efficacy of immunotherapy in lung cancer patients. Moreover, multiple basic studies have reported that the gut microbiota affected the therapeutic effect of chemo-radiotherapy in lung cancer (37, 38), suggesting that modulating the gut microbiota was an important way to improve chemo-radiotherapy sensitivity. However, only two clinical trials of immunotherapy combined with probiotics for lung cancer were searched, with the registration number NCT04699721/ NCT05094167.…”
Section: Evolution Of Research Hotspots and Frontiersmentioning
confidence: 99%
“…Briefly, l-histidine and the imidazole propionate (ImP) produced by the gut microbiota have protective effects against radiation-induced lung and heart toxicity [ 169 ]. Fecal microbiota transplantation (FMT) can alleviate radiation pneumonia and improve lung function in mice [ 170 ]. Qin et al [ 99 ] showed that phycocyanin could attenuate the lung inflammation and fibrosis induced by radiation via regulating the imbalance of the lung and gut microbiota caused by radiotherapy in mice.…”
Section: Radiotherapy For Cancer Based On the Gut Microbiotamentioning
confidence: 99%